Flood Modeling on Koya Catchment Area Using Hyfran, Web Map Service, and HEC-RAS Software - Dawood, Anwer H.; Mawlood, Dana K.; Al-Ansari, Nadhir (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2021)
In this research, The boundaries of the Koya catchment area have been delineated, and valley paths in the region were drawn by using the Water Modeling System (WMS) software, Analysis of the morphometric information indicated that the morphometric characteristics of watersheds contribute to the floods. The average surface runoff depth depends on the curve number values that are determined based on the types of soil cover and soil class according to Harmonized World Soil Database HWSD software that indicates the soil class in the study area are Group B silt loam, The results obtained also show that the potential for surface runoff varies with land use and soil characteristics. Also, the value of the curve number (CN) was determined to be 71. The hydrological modeling was performed by the HEC-HMS program that simulates the process of rainfall to runoff using the SCS curve number model. A flood hydrograph was constructed at the catchment area outlet and the floodplain delineation was verified by the HEC-RAS software. The results indicated that the 100-year return period flood could Reach critical areas such as the urban area, agricultural area, residential areas. the results of this study indicate that there are suitable sites in the catchment areas for constructing small dams and ponds for water harvesting.